Bioactive Compounds from Penicillium sp. Inhibit Antiapoptotic Bcl-2, Bcl-XL and Mcl-1: An in silico Study - Massardi, Adhie; Bahry, Sandy Samsul; Rahmawati, Nur Anindya; Shabirah, Carissa Azmi; Pangastuti, Artini (Cell and BioPharmaceutical Institute, 2023)
Background: Antiapoptotic Bcl-2 proteins are overexpressed in cancer cells, leading to inhibition of apoptosis and the development of therapeutic resistance. Targeting only one type of antiapoptotic protein may have limited efficacy in cancer therapy. Anticancer drugs capable of inhibiting Bcl-2, Bcl-XL and Mcl-1 simultaneously are necessary to be explored. Penicillium sp. produces various bioactive compounds with anticancer, antibacterial, and antiviral activities. The aim of this research was to determine the best bioactive compound candidates for inhibiting Bcl-2, Bcl-XL, and Mcl-1 proteins.Materials and methods: Molecular docking analysis was conducted to estimate the binding affinity of Penicillium sp. bioactive compounds with Bcl-2, Bcl-XL, and Mcl-1 proteins. Compounds with the lowest binding energies were visualized using PyMol and Ligplot+ and further subjected to drug-likeness testing based on Lipinski's rule of five.Results: Bioactive compounds with the highest binding affinities were verruculogen and wortmannin. Wortmannin complied with Lipinski's rule of five. Meanwhile, verruculogen violated one out of the five rules by having a molecular weight >500 Da. Both compounds could be used as oral drugs.Conclusion: Verruculogen and wortmannin from Penicillium sp. show significant potential as oral anticancer drug candidates.Keywords: Bcl-2, Bcl-XL, Mcl-1, Penicillium sp., in silico